1996
DOI: 10.1042/cs0900255
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Status and Lipid Peroxidation in Type II Diabetes Mellitus with and without Complications

Abstract: 1. This study was conducted on 467 cases of non-insulin-dependent diabetes mellitus and 180 healthy controls. Lipid peroxidation products in plasma and erythrocytes were assayed as thiobarbituric acid reactive substances, along with the erythrocyte antioxidant enzymes, namely superoxide dismutase, catalase and glutathione peroxidase. In addition, scavenger vitamins A, C and E and reduced glutathione levels in blood were also measured. 2. Lipid peroxidation was significantly raised within the first 2 years of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
133
4
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(162 citation statements)
references
References 9 publications
19
133
4
6
Order By: Relevance
“…Previously reported increases in plasma F 2 -isoprostanes and their diminution in diabetes with antioxidant vitamins referred to patients with poorer glycaemic control than our study group [29,30]. We found that plasma antioxidant capacity was decreased in our patients in agreement with previous reports showing that diabetic patients have decreased plasma concentrations of antioxidant vitamins [32]. However, low plasma ORAC was not corrected by CoQ supplementation, suggesting that CoQ might not contribute to plasma antioxidants measured by this assay.…”
Section: Discussionsupporting
confidence: 90%
“…Previously reported increases in plasma F 2 -isoprostanes and their diminution in diabetes with antioxidant vitamins referred to patients with poorer glycaemic control than our study group [29,30]. We found that plasma antioxidant capacity was decreased in our patients in agreement with previous reports showing that diabetic patients have decreased plasma concentrations of antioxidant vitamins [32]. However, low plasma ORAC was not corrected by CoQ supplementation, suggesting that CoQ might not contribute to plasma antioxidants measured by this assay.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are similar to results of other investigators studying antioxidant vitamins in relation to risk factors in diabetic subjects [18,45]. The sex of diabetic or control subjects had no significant influence on a -tocopherol levels.…”
Section: Discussionsupporting
confidence: 82%
“…Some investigators have reported an association between TBARS and diabetic complications [16,18] while other have not [14]. Jennings et al [41] reported that elevated levels of conjugated dienes in plasma from diabetic subjects are associated with microangiopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations